Developing pop-up book teaching materials on polyhedron to improve junior high school students' mathematical literacy - Puspaningrum, Brilliant Cahya; Istihapsari, Vita (International Journal on Education Insight, 2023)
This research was motivated by the problems found at SMP N 1 Bantul, a junior high school in Bantul regency, Yogyakarta, which were obtained by conducting interviews with mathematics teachers. We found that there were still many students who had not received good stimulation in cognitive development at the concrete stages so that when entering the formal stages students have difficulty to make reasoning into more complex problems where this reasoning will affect students' mathematical literacy skills. Besides, they also lack of teaching materials especially in grade 7 due to using the new curriculum. One of which are the material of polyhedron which only explains concepts in general and does not explain further than the elements, content, and spatial components as well as the visualization of geometric shapes. This study aims to develop pop-up book teaching materials on polyhedron to improve the students' mathematical literacy skills. This development research used the analysis, design, development, implementation, and evaluation (ADDIE) model involving students of class VII-A in the testing. Before conducting testing in the classroom, the teaching materials, pretest, and posttest were validated by experts. The results are: (1) scores of material experts and media experts gave a valid result; (2) the students and teachers responses to teaching materials gave practical testimonies; and (3) there was an average increase from pretest to posttest results at 25.49 points.